(3GdEYdGe HaVGFd GdTGes - (3CMeO Hf Ydj Hf YeQ Hf UGdM, TgGH GdOjf, CHh GdfLGM Gdnepfjfj,J (B1172 (3g` s
(3ChdgG (B:s
(3CeG HYO ajbhd abjQ QMeI QHg hGSjQ hUeI PfHg CMeO Hf Ydi GdYKeGfj GdTgjQ HGdefjfi s
(3BNQgG (B:s
(3SMGH QMeJg hQMeGfg Hg ai OGQ cQGeJg ajeG jJYdb HGdeQGe ef LeY gPg GdCQbGe s
(3QJHg KeGfjI CHhGH hHg JQGLe deYGUQjgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B181 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B15s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B282 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B21 s
Keywords: (3GdJGQjNs